Evaluation of Transit Signal Priority for Bus Rapid Transit in Heterogeneous Traffic Flow - Mohammadhossein Abbasi* (Faculty of Mechanical Engineering in Slavonski Brod, Faculty of Electrical Engineering in Osijek, Faculty of Civil Engineering in Osijek, 2021)
Inefficient traffic signal control at intersections causes vehicle delays, increased fuel consumption, and vehicle emissions. With respect to the large number of fixed signalized intersections along the 7th line of Tehran BRT, passengers experience long delays and travel time while BRT is defined as a high-quality bus-based transit system that delivers fast and efficient service according to literature. Due to constraints on increasing supply, actuated traffic signal (ATS) and public transportation priority (PTP) are some of the possible signal control methods that can reduce the above-mentioned problems. In this paper, the 7th line of Tehran BRT is simulated using Aimsun. ATS and PTP have been simulated and traffic, environmental and economic indicators of transit and non-transit vehicles have been derived. Finally, a cost-benefit analysis is conducted to calculate the net present value (NPV), internal rate of return (IRR) and payback period (PP) of investment. Results show a decrease in travel time, delay, stop time, fuel consumption and pollutant emissions and an increase in average speed and flow at intersections. The payback period is estimated to be approximately two months, indicating a short-term policy and other economic indices confirm the profitability of project.